PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEMADAMAN LISTRIK OLEH PT. PLN (PERSERO) SUB RAYON PULAU KIJANG (STUDI KASUS PEMADAMAN LISTRIK SEPIHAK DI KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR) - Hasanah, Ulfia; ', Rahmita; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Today electricity is a very urgent need for the society because most people needs rely on electrical energy. The increasing demand for electricity is not balanced with the availability of electricity by the electricity company PT PLN. It causes electricity services to be not optimal and consequently harm the public or electricity consumers. Likewise, the services of electricity by PT. PLN (Persero) Sub Rayon Pulau Kijang to consumers of electricity in the District Reteh, electricity outages still occur to unilaterally causing harm to consumers.This research entitled Consumer Legal Protection against Electricity Outages by PT. PLN (Persero) Sub Rayon Pulau Kijang (Case Study: Electricity Outages Unilaterally in District Reteh, Indragiri Hilir. The formulation of the problem is how the rights of consumers in the service of electricity by PT. PLN (Persero) Sub Rayon Pulau Kijang, legal protection of electricity consumers in District Reteh against electricity outages unilaterally by PT. PLN (Persero) Sub Rayon Pulau Kijang, and the responsibility of PT. PLN (Persero) Sub Rayon Pulau Kijang to the rights of electricity consumers in District Reteh.The research aimed to determine the rights of consumers in the service of electricity by PT. PLN (Persero) Sub Rayon Pulau Kijang, the legal protection of electricity consumers in District Reteh against electricity outages unilaterally by PT. PLN (Persero) Sub Rayon Pulau Kijang and the responsibility of PT. PLN (Persero) Sub Rayon Pulau Kijang to the rights of electricity consumers in District Reteh.Type of research was a sociological law that was conducting research directly to the location or studied point. The nature of study was descriptive, by using primary and secondary data sources. Data collecting techniques used were questionnaire, interview and library research. Data analysis used was qualitative, and a method of conclusion used was deductive.The results showed consumer rights in the service of electricity by PT. PLN (Persero) Sub Rayon Pulau Kijang performed poorly due to Chief of Branch and Employee of Operator / Services Disruption, Staff of Public Service in District Reteh, and electricity consumers were not aware of consumer rights. there was no legal protection of Electricity consumers against electricity outages unilaterally. There was no responsibility of PT. PLN (Persero) Sub Rayon Pulau Kijang to the rights of electricity consumers in District Reteh.Leaders and employees of PT. PLN (Persero) Sub Rayon Pulau Kijang should increase the knowledge of the business operators of electric power and the rights of electricity consumers; conduct counseling and provide legal protection of electricity consumers in District Reteh related to electricity outages unilaterally, have a responsibility to the rights of electricity consumers in District Reteh; and electricity consumers in District Reteh increase knowledge about the rights of electricity consumers.Keywords: Consumer Protection, Electricity Outages